KEMAMPUAN MENULIS SURAT PRIBADI SISWA KELAS VII MTs AL-ITTIHAD RUMBAI - M.Ridho.AR '; Nursal Hakim; Charlina ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study titled Writing Ability Personal Letter VII MTs Al-Ittihad Rumbai.. This study aims to determine the level of writing ability personal letter of class VII MTs Al-Ittihad Rumbai. The method used is descriptive analysis method with qualitative approach. Data of this study is to test write personel letters. (1) The results of this study found the ability to write the place and date of the letter student class VII MTs-Al-Ittihad Rumbai. (2) The ability of a salutation. (3)The ability to write a personal letter student class VII MTs-Al-Ittihad Rumbai. (4) the ability to write greeting cover. (5) The ability to write signatur. Of the six aspects that I researched it chan be concluded that the student class VII MTs-Al-Ittihad Rumbai have the ability to moderate with a score of 70.Key Words: Writing Skills, Personal Letter, Student Class VII MTs Al-Ittihad